Irrigant and intracanal medicament choices in routine endodontic practice: A cross-sectional survey of British general dentists - Stefan V. Stefanescu; Maria Mihaela Iuga; Claudia Panzetta; Mauro Colangeli; Fernando Espada Salgado; Kavalipurapu Venkata Teja; Kaligotla Apoorva Vasundhara (Saudi Endodontic Journal)
Introduction: Choices vary among clinicians due to personal preference or experience with disinfectants during clinical practice. Hence, the present survey aimed to evaluate the rationale behind the selection of endodontic irrigants and interappointment medications and to compare therapeutic approaches among British general dental practitioners (GDPs) with varying years of experience. Materials and Methods: A structured online questionnaire consisting of 14 questions was distributed to attendees at a dental conference in England via a QR code, along with a formal invitation to participate in the research. A sample size calculation determined the minimum required sample size of 377 GDPS from a population of 2356 British GDPs. To assess the impact of experience on disinfection protocols, clinicians were categorized by years of experience to better understand any generational differences in clinical concepts. The responses were analyzed using the Chi-square test (P < 0.05), with a 95% confidence level and a 5% margin of error. Results: Four hundred and twenty GDPs responded to the survey, representing 17.82% of the GDPs attending the conference. The results showed that sodium hypochlorite (NaOCl) is the most commonly used irrigant, with 96% (403) of respondents selecting it, and no significant differences were found between generational groups. Regarding the most important criteria for selecting an irrigant, 59.9% (243) of respondents considered NaOCl to be the most effective. Calcium hydroxide was the primary interappointment medication, used by 92.6% (389) of respondents. When grouped by years of experience, the only notable difference was in the duration for which medication remained in the root canal. Clinicians with more experience tended to leave the medication in the canal for longer periods. Conclusion: Experience was found to be the most significant factor in the choice of interappointment medication, whereas it had less influence on the selection of irrigants. The therapeutic approach varied more significantly between GDPs in different experience groups, suggesting that evolving materials and techniques in endodontics influence clinical protocols and the attitudes of practitioners.